A Rapidly Convecting Lava Lake at Masaya Volcano, Nicaragua - Pering, Tom D.; Ilanko, Tehnuka; Wilkes, Thomas C.; England, Rebecca A.; Silcock, Siân R.; Stanger, Leigh R.; Willmott, Jon R.; Bryant, Robert G.; McGonigle, Andrew J. S. (Frontiers in Earth Science, 2019)
The recent lava lake activity at Masaya volcano (Nicaragua), which commenced in 2015, displayed several unusual phenomena. We report for the first time on the dynamics of this rapidly convecting lake, which, to the best of our knowledge manifested the highest flow velocities ever reported for a lava lake: 13.7 – 16.4 m s-1, in addition to unprecedented fluid dynamic behaviour such as waterfall-like fluid flow patterns. We studied this system with multiparametric and high time resolution remote sensing measurements, performed during June 2017, including ultraviolet camera observations of SO2 emission rates, near infrared thermal camera measurements and video analyses of the lake surface. Median SO2 emission rates of 3.1 (± 0.8) and 3.7 (± 0.9) kg s-1 were found, which are lower than previously published estimates, and consistent with waning lava lake behaviour. Video analyses enabled characterisation of frequent bursts of spherical-cap bubbles on the surface and calculation of individual bubble masses. We show that only a small fraction, 7-8%, of total SO2 emission volumes are contributed by these bubbles. Furthermore, periodicity analysis reveals regular 200-300s oscillations in SO2 emissions. These are not shared by any of our other dataset, hence we tentatively assign an atmospheric causal generation mechanism to them. Overall, we highlight the truly unique behaviour of this short-lived lava lake.